1998
DOI: 10.3171/jns.1998.88.6.1111
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenoma producing growth hormone and adrenocorticotropin: a histological, immunocytochemical, electron microscopic, and in situ hybridization study

Abstract: The authors report on the morphological features of a pituitary adenoma that produced growth hormone (GH) and adrenocorticotropic hormone (ACTH). This hormone combination produced by a single adenoma is extremely rare; a review of the available literature showed that only one previous case has been published. The tumor, which was removed from a 62-year-old man with acromegaly, was studied by histological and immunocytochemical analyses, transmission electron microscopy, immunoelectron microscopy, and in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 15 publications
2
35
1
4
Order By: Relevance
“…This hormone combination of ACTH and GH, produced by a single adenoma with hormone-secreting symptoms, has also been previously reported [9][10][11]. However, to our knowledge, a silent corticotroph adenoma with GH production, such as in our case, has never been reported.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This hormone combination of ACTH and GH, produced by a single adenoma with hormone-secreting symptoms, has also been previously reported [9][10][11]. However, to our knowledge, a silent corticotroph adenoma with GH production, such as in our case, has never been reported.…”
Section: Discussionmentioning
confidence: 49%
“…Cavernous sinus syndrome, in which a pituitary adenoma extends laterally into the cavernous intracranial sinus, is an uncommon complication of pituitary apoplexy [8]. In addition, a pituitary adenoma producing both ACTH and GH is highly unusual [9][10][11]. We report a unique case of a 30-yearold man with corticotroph cell adenoma, without acromegaly or other features typical of Cushing's disease, who presented with cavernous sinus syndrome following pituitary apoplexy.…”
mentioning
confidence: 99%
“…In bimorphous and plurimorphous adenomas, each hormone is produced by different cell populations, and almost all possible combinations of hormone productions involving GH and PRL, GH, PRL, glycoprotein hormone subunit ( GSU), TSH or FSH have been observed (Felix et al 1994, Furuhata et al 1994, Gessl et al 1994, Gil-del-Alamo et al 1994, Bertholon-Gregoire et al 1999. Although these combinations of hormones correspond to the differentiation of the cell lineages, it has been reported that very occasional cases of bimorphic pituitary adenomas produce adrenocorticotropic hormone (ACTH) and GH in different cell populations (Arita et al 1991, Kovacs et al 1998. We have recently encountered a monomorphous pituitary adenoma that produces both ACTH and GH in the same cell.…”
Section: Introductionmentioning
confidence: 91%
“…Finally, these data may provide insight into the molecular mechanism by which both ACTH and GH, which are normally expressed in different cell lineages, were produced in the same cells in a monomorphous human ACTH-secteting adenoma (Arita et al 1991, Kovacs et al 1998, Tahara et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Kovacs et al 14 , classificam os tumores produtores de mais de um hormônio em monomorfos, dimorfos e plurimorfos conforme a célula tumoral seja de linhagem mono ou pluriclonal, salientando que os adenomas são monoclonais e que nestes casos haveria alguma mutação na célula primitiva de origem. Em relação à casuística de Saeger 15 , que segue a classificação do Clube de Patologia Hipofisária de Paris, também temos diferenças como exposto na Tabela 9.…”
Section: Discussão Discussãounclassified